Integration of wind energy systems into the grid: power quality and technical requirements - Madangombe, Taruziwa (Department of Electrical Engineering, 2014)
The integration of wind energy into the utility network has increased significantly over the past years largely as a result of the increasing environmental concerns arising from the use of fossil fuels, coupled with the anticipated global increase in oil. In South Africa, the wind energy industry is still in its infancy, with the Klipheuwel (about 3.2 MW) and Darling (about 4.2 MW) wind farms being the only grid connected projects in the country. However, grid integration studies carried out in [1] have shown that there are over 7 000 MW potential ideas for wind power in the Western Cape alone and this is a clear indication that there is a growing interest in wind development locally. The Government has also set a 4% target for the development of the renewable energy in the country by 2013. In light of the above, this thesis discusses some of the technical requirements and power quality issues that need to be addressed in order to fully integrate wind power into the network without adversely affecting the operation of the grid. These have been researched through reviewing the various standards and grid codes for wind power that have been implemented in other leading countries, in order to identify some of the requirements that can be adapted to suit our local integration process. Some of the main technical issues that are discussed in this thesis include the strength of the grid (fault levels), permitted penetration levels, choice of wind turbine and the reactive power requirements of the network. All these issues contribute towards the resolution of the impact of wind turbines on the power quality of the network, especially at the point of common coupling or connection (PCC). Various power quality phenomena were discussed in the literature but the ones that were further investigated included the voltage level profile, harmonic distortions as well as reactive power requirements from the wind turbines. These were determined both during the steady operation of the network and during a network disturbance.